A study on knowledge, attitude, and practices related to brucellosis among small-scale dairy farmers in a rural area of Belagavi, Karnataka - Patil, Darshan; Reddy, Chelikam Veeraraghavendra; Revagoud, Kalmeshwar; Sarawade, Ravindra (International Journal Of Community Medicine And Public Health, 2026)
Background: Brucellosis remains a significant zoonotic disease affecting livestock productivity and human health in India. Despite the high burden in Karnataka, little is known about farmers’ knowledge, attitudes, and practices (KAP) in rural Belagavi. This study aimed to assess KAP related to brucellosis among small-scale dairy farmers to identify behavioural gaps influencing disease transmission. Methods: A community-based cross-sectional study was conducted among 188 small-scale dairy farmers in rural Belagavi. Data were collected using a pre-tested structured questionnaire covering socio-demographic characteristics and KAP components. Descriptive statistics were used to summarise responses, and associations were assessed using Chi-square or Fisher’s exact tests. Results: Awareness of brucellosis was limited, with 53.2% having never heard of the disease and 52.4% demonstrating poor knowledge scores. Most participants were unaware of zoonotic transmission (84.6%) or human symptoms (76.1%). Despite these gaps, attitudes were predominantly positive, with all participants scoring within the favourable range. Several risky practices were identified: 93.6% sold unpasteurized milk, protective measures during handling of aborted materials were minimal, and only 6.9% reported adopting any preventive or vaccination-related precautions. Although 96.8% sought veterinary care for sick animals, most relied on family advice for general animal health decisions. Conclusions: Farmers exhibited substantial knowledge gaps and unsafe practices despite positive attitudes toward disease prevention. Strengthening community-based education, improving awareness of zoonotic risks, and promoting safe livestock-handling behaviours are essential for effective brucellosis control in this high-risk population.